(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The goal of this study was to produce a topical gel formulation of Diclofenac diethylamine using various gelling agents, such as carbopol 934, Sodium Carboxy methyl cellulose, and alovera extract, to reduce the gastrointestinal side effects associated with oral administration. Topical medication administration can be accomplished by integrating into the gel matrix, preventing first-pass metabolism and allowing for greater local action in anti-inflammatory and analgesic purpose. The gel formulations were tested for homogeneity, grittiness, viscosity, pH, spreadability, drug content, in vitro drug release and release kinetics. The effects of polymer composition on the rate of drug release from the gel formulations were examined through dialysis membrane at 37º ± 0.5ºC. The gel formulation consisting of alovera extract (F3) was found to be suitable for topical application based on in vitro evaluation. These results suggest the feasibility of the topical gel formulation of Diclofenac diethylamine.